Facebook, Silaturahmi, dan Budaya Membaca: Studi Hubungan antara Penggunaan Situs Jejaring Sosial (Facebook) dengan Budaya Silaturahmi dan Membaca di Kalangan Mahasiswa FISHUM UIN Sunan Kalijaga Yogyakarta - Fatma Dian Pratiwi (Program Studi Ilmu Komunikasi, 2010)
This article tends to explain the correlation between using Facebook as social network site with the culture of silaturahmi and reading in FISHUM's students of UIN Sunan Kalijaga Yogyakarta. Using the survey method, the population of the research was 216 students from Psychology, Sociology, and Communications department class of 2008. This research found that there was no correlation between using Facebook and silaturahmi conduct by students. Proved by statistics analysis using SPSS for Windows 12,0 correlation coefficient (r): 0,078 with the p grade- 0,255. But there was correlation between using Facebook and reading culture with the correlation coefisien (r): 0,259 with the p grade= 0,000. From that statistic analysis, we can conclude that being a Facebook member not automatically make the students loose contact especially by face-to-face communication with their friends. But in term of reading culture, being member of Facebook is correlated with the low quality of reading culture.